The Sustainable Development Path of the Gold Exploration and Mining of the Sanshan Island-Jiaojia Belt in Laizhou Bay: A DID-SVAR Approach - Sheng Zhang (MDPI AG, 2021)
Gold is a vital strategic resource, and it plays an irreplaceable role in maintaining national financial security, enhancing currency guarantee capabilities, and serving as a country’s last means of payment. Gold plays an essential role in several fields that are vital to sustainable development. In 2020, an ultra-large-scale gold deposit spanning land and sea was discovered in Sanshan Island-Jiaojia Belt, Laizhou Bay, China. Its owner, Shandong Gold Group, also established Sanshan Island as a new ecological mine model. Applying a difference in differences-structural vector autoregression (DID-SVAR) approach, our research found that the whole biodiversity of Laizhou Bay decreased by 0.27% purely due to gold exploration in Sanshan Island-Jiaojia. In the long run, gold mining will have an apparent 2.9% adverse effect on marine products, and fishing for marine products will have a 2.1% adverse effect on marine products themselves.